The Microbial Isolates of the Human Axilla Among Some Students and Employees of the College of Education –Ibn Al-Haitham, University of Baghdad - Ibrahim, I. A-J; AL- Hadaria, S A-M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Body odour is the smell caused by bacteria feeding on sweat on the skin, especially in the armpit and groin area. Fifty-four volunteers from students and employees of college of Education Ibn Al- Haitham, were surveyed. Data were obtained concerning: subject details and microbial examination. The following conclusions were reached:  1) coagulase negative Staphylococcus was the most common isolate. 2) The most effective antibiotics were amikacin, ciprofloxacin, vancomycin, cephalothin, tobramycin, gentamycin respectively and were least sensitive to methicillin and penicillin G. 3) Alum zirconium and alum chlorohydrate were the most effective antiperspirants.